Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae) - Weissman, David B.; Gray, David A. (Zootaxa, 2019)
Gryllus field and wood crickets of the United States, mostly west of the Mississippi River, are reviewed and revised. We validate the following 18 Gryllus cricket names: G. armatus, G. assimilis, G. brevicaudus, G. cayensis, G. cohni, G. firmus, G. fultoni, G. integer, G. lineaticeps, G. multipulsator, G. ovisopis, G. pennsylvanicus, G. personatus, G. rubens, G. texensis, G. veletis, G. vernalis, and G. vocalis. We synonymize G. alogus under G. vocalis. We designate a lectotype for G. armatus. We describe the following 17 new Gryllus species: G. chisosensis, G. leei, G. lightfooti, G. longicercus, G. makhosica, G. montis, G. navajo, G. planeta, G. regularis, G. saxatilis, G. sotol, G. staccato, G. thinos, G. transpecos, G. veintinueve, G. veletisoides, and G. vulcanus. We present biology, distribution, and genetic analysis of all taxa and discuss their nearest relatives.